The Effect of Integrated Reporting on Firm Value with Good Corporate Governance as a Moderating Variable - Akbar, Ulya Amadyra; Umyana, Ayu (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to investigate the relationship between integrated reporting and firm value, using the audit committee, a component of good corporate governance, as a moderating variable. The approach used in this research is quantitative. Firm annual reports from the Indonesia Stock Exchange website served as the main source of the secondary data used. Twelve manufacturing firms that were listed on the IDX and featured in the LQ-45 index between 2021 and 2023 make up the study's population. A purposive selection strategy was used to choose the sample, from which 36 observations were gathered. The tests that used and included in this study are moderated regression analysis (MRA), traditional assumption testing, descriptive statistical testing, and hypothesis testing. The study's findings demonstrate that integrated reporting has a substantial impact on firm value and that the audit committee acts as a moderating factor to strengthen the association between the two.